2017
DOI: 10.1097/bco.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

Early results of partial capitate shortening osteotomy in management of Kienböck disease

Abstract: Background: Capitate shortening is the best decompression procedure in the management of Kienböck’s disease in patients with ulnar neutral or positive variance, although carpal collapse develops inevitably. The current study was to report our experience in partial capitate shortening osteotomy as an alternative procedure. Methods: This was a prospective study of 20 patients with Lichtman stage II and IIIa Kienböck’s disease managed by partial capitate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Weighted mean grip strength as a percentage of the contralateral side was obtainable for most studies; capitate shortening osteotomy: 68.0% (three studies, n ¼ 26) 21,23,24 ; radial shortening osteotomy: 75.2% (four studies, n ¼ 35) 21,22,25,30 ; VBG: 88.2% (five studies, n ¼ 45) 13,22,27,28,31 ; PRC: 70.0% (two studies, n ¼ 17). 19,29 Ten studies showed grip strength improvement, while 11 did not report preoperative grip strength and 1 had incomplete data.…”
Section: Stage-iiia Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Weighted mean grip strength as a percentage of the contralateral side was obtainable for most studies; capitate shortening osteotomy: 68.0% (three studies, n ¼ 26) 21,23,24 ; radial shortening osteotomy: 75.2% (four studies, n ¼ 35) 21,22,25,30 ; VBG: 88.2% (five studies, n ¼ 45) 13,22,27,28,31 ; PRC: 70.0% (two studies, n ¼ 17). 19,29 Ten studies showed grip strength improvement, while 11 did not report preoperative grip strength and 1 had incomplete data.…”
Section: Stage-iiia Resultsmentioning
confidence: 98%
“…Weighted mean VAS for patients who underwent capitate shortening osteotomy was 3.2 (three studies, n ¼ 26). 21,23,24 Despite heterogeneous pain reporting for radial shortening osteotomy, there were seven patients who were pain free, 19 had mild pain, and 1 had moderate pain at final follow-up (four studies, n ¼ 27). 21,22,25,26 VBG pain scores were also heterogeneous.…”
Section: Stage-iiia Resultsmentioning
confidence: 99%
“…2). [31][32][33][34] Capitate Shortening Almquist 19 recommended capitate shortening for Kienbock's disease in ulnar positive wrists. Various techniques have been reported and are presented in ►Table 1.…”
Section: Fixation Optionsmentioning
confidence: 99%
“…However, patients with a lower Lichtman grade did have better outcomes. [32][33][34][35] Single-Cut Single-Screw Capitate-Shortening Osteotomy…”
Section: Fixation Optionsmentioning
confidence: 99%
See 1 more Smart Citation